Trends of cervical tumours amongst women from perspectives of demographic, socioeconomic and geographic indicators: retrospective ecological study in Czechia - Holy, Ondrej; Machaczka, Ondrej; Schovankova, Tereza; Navratilova, Daniela; Zimmermannova, Jarmila; Klasterecka, Romana; Vevoda, Jiri (Frontiers in Public Health, 2024)
Introduction For many infectious diseases, women are at higher risk and have a more severe disease course than men for many reasons, including biological differences, social inequalities, and restrictive cultural norms. The study focuses on infections with human papillomaviruses (HPV) in the form of cervical cancer as a gender-specific disease. The main goal is to evaluate cervical tumour incidence trends in the Czech female population in the HPV vaccination period 2012–2020 in relation to selected demographic, socioeconomic, and geographic indicators. Methods This is a retrospective ecological study. Data from publicly available databases about the incidence and mortality of cervical tumours (C53 Malignant neoplasm of cervix uteri, D06 Carcinoma in situ of cervix uteri according to ICD 10) and HPV vaccination rate were analysed and compared with demographic, socioeconomic and territorial data. Associations were searched using correlation analysis. Results There was a decreasing trend in the incidence of cervical cancer in the observed period. Regarding cervical tumours (C53, D06) and malignant neoplasm of cervix uteri incidence (C53), the decrease was approximately 11 and 20%, respectively. Differences between regions were observed in incidences and vaccination rates. Based on correlation analysis, indicators connected with urban/rural aspects, such as a share of urban population and population density, were statistically significant. The indicators related to higher cervical cancer incidence are the high unemployment rate of women, the high number of divorces, the high number of abortions, the high share of the urban population, the high number of students, and the high number of women with only primary education. On the other hand, the indicators related to lower cervical cancer incidence are the high gross domestic product (GDP), the high average gross monthly wage per employee, the high employment rate of women, the higher average age of mothers at birth, and the high number of women with tertiary education. Conclusion Results underline the problem of economically disadvantaged regions and families. Increasing vaccination rates, promoting regular screening for cervical cancer, and supporting awareness in the population, especially in regions with higher incidence rates, should be priorities for public health efforts.